Managing wolf impacts on sheep husbandry: a collaborative implementation and assessment of damage prevention measures in an agricultural landscape - Salvatori, Valeria; Marino, Agnese; Ciucci, Paolo; Galli, Claudio; Machetti, Massimo; Passalacqua, Edoardo; Ricci, Simone; Romeo, Giorgia; Rosso, Fabio; Tudini, Lucia (Frontiers in Conservation Science, 2023)
Wolves in Europe are expanding their range and significantly impacting farming livelihoods and landscapes. Damage prevention measures such as livestock guarding dogs and night-time enclosures have proven successful in mitigating losses. However, they are often implemented as top-down measures without a proper understanding of the farming dynamics they are meant to alter, making them unappealing and difficult to implement for farmers. Semi-extensive, small scale livestock farming systems are particularly vulnerable and diverse, requiring specific care and catered support when addressing issues related to wildlife management. In these contexts, it is crucial to employ adaptive management approaches that enable solutions to be collaboratively designed at the grassroots level. Here we propose a method for centring the experiences and knowledge of local farmers to co-produce damage prevention practices that better address their needs. We developed this approach in the course of the LIFE MEDWOLF project, which was implemented in the province of Grosseto, Italy, between 2012 and 2017. The project brought together local authorities, environmental associations, farming unions and individual farmers to develop tailor-made damage prevention measures and assess their technical and economic impact, through a stepwise process. Collaboration with 86 local farmers resulted in >50 modifications to the original project plan, and an overall 50% reduction of preyed livestock in farms that participated in the project. Our findings highlight the benefits of collaboratively designing, implementing, and monitoring damage prevention measures with farmers. Based on these results, we reflect on the importance of integrating local and scientific knowledge, on the implications this has had on stakeholder relations, and on the challenges that we faced in upscaling this management approach.